Benchmarking for locally tuned sustainability: The case of energy and water use in New Zealand vineyards - Vicent Gasso; Andrew Barber; Henrik Moller; Enrique Bayonne; Frank W. Oudshoorn; Claus G. Sørensen (Environmental and Sustainability Indicators)
Sustainability benchmarking is the process of comparing indicators of performance with other organizations to identify, adapt and implement best practice approaches for sustainability improvement. The benchmarking process is more likely to incentivise and guide sustainable practice if it is based on fair and sensible comparisons, accommodating features such as local biophysical and economic constraints, in order to place all farmers on a “level playing field”. This study developed a benchmarking rationale accommodating local opportunities and constraints for effectively incentivising locally-tuned sustainability improvements. This was carried out by analysing energy and water use on the 1103 vineyards enrolled in the Sustainable Wine-growing New Zealand scheme. Regression models to predict spatial and temporal variations of energy and water use explained relatively large proportions of the resource use variance. Production area and region were common and significant predictors of resource efficiency. A 59% increase over time in fuel efficiency took place in vineyards instigating energy reduction plans and actions. The vineyards' rank performance differed widely when benchmarked within the entire sector or within other vineyards of equivalent characteristics, specifically for agroecological and production related characteristics influencing performance. For example, one vineyard ranked at the 20 percentile in fuel efficiency within the sector, yet at the 75 percentile when compared against vineyards in its own region and with a similar production area. Aggregated and non-locally tuned benchmarking might best suit consumers and national-level policy makers, but they do not capture the local and diverse challenges faced by the individual farmers. Use of locally-tuned benchmarking approaches can better identify actual sustainability improvement opportunities and may enhance farmers’ trust in the sustainability exercise, improve participation and better incentivise change towards sustainability.